Collective memory work as an unsettling methodology in tourism. Issue 1 (10th February 2021) - Grimwood, Bryan S. R.; Johnson, Corey W.
Abstract: Research has exposed how colonial power relations operate in and through various domains of tourism. As byproducts of Western academia, tourism research and education are significant sites where the structures, systems, and narratives of Settler colonialism can become further entrenched and legitimized. What research methodologies can challenge the colonial complexion of tourism research and enable tourism students and scholars to confront how their identities and responsibilities are tethered to (Settler) colonization? We argue that collective memory work (CMW), a participatory and participant-focused methodology, can contribute to these disruptive aims by examining individual experience as embedded and imbued with social meaning. Our ultimate objective is to situate, articulate, and reflect on the use of CMW as an unsettling methodology in tourism research and education contexts. Since 2016, we have used CMW to engage Settler Canadian graduate students in a process of critically analyzing individual memories and collective experiences of tourism and Indigenous–Settler relationships. After establishing theoretical and political contexts of Settler colonialism, we present an overview of CMW's feminist and transformative underpinnings and explain how these are being adapted into the methods of our ongoing research with students. Preliminary insights from this research illuminate CMW as a consciousness-raising pedagogical methodology that, in focusing in on Settler memory narratives, helps make space for decolonization in tourism and tourism research.